The relationship between endothelial function and aortic valve calcification: Multi-Ethnic Study of Atherosclerosis. (January 2019) - Abd alamir, Moshrik; Goyfman, Michael; Johnson, Dana; Liu, Yangyang; Dabbous, Firas; Chaus, Adib; Budoff, Mathew
Abstract: Background and aims: Aortic valve calcification (AVC) may be associated with atherogenic processes arising from endothelial dysfunction (ED). Limited data is available about the relationship between ED, defined by flow mediated dilation (FMD%) and biomarkers, and the prevalence and progression of AVC in a multiethnic population. Methods: A sample of 3475 individuals from the Multi-Ethnic Study of Atherosclerosis (MESA), with both initial and repeat CT scans at a mean of 2.65 ± 0.84 years and FMD% and serologic markers of ED [ C-reactive protein (CRP), Von Willebrand factor (vWF), Plasminogen Activator Inhibitor (PAI), fibrinogen, Interleukin 6 (IL6), E-selectin and ICAM-1 (Intercellular Adhesion Molecule 1)], were analyzed. Multivariate modeling evaluated the association between ED and the prevalent AVC and AVC progression. Results: The median levels of FMD% was lower and vWF%, fibrinogen, IL6 and ICAM-1 were significantly higher in the AVC prevalence group versus no AVC prevalence (all p < 0.001). In the fully adjusted model for established risk factors, decreasing FMD% or increasing biomarkers was not independently associated with AVC prevalence [OR FMD% 1.028 (0.786, 1.346), CRP 0.981 (0.825, 1.168), vWF 1.132 (0.559, 2.292), PAI 1.124 (0.960, 1.316), fibrinogen 1.116 (0.424, 2.940), IL6 1.065 (0.779, 1.456), E-selectin 0.876 (0.479, 1.602) and ICAM-1 1.766 (0.834, 3.743)]. In the AVC progression group, FMD%, vWF%, fibrinogen and IL6 were significantly different ( p < 0.05). After adjusting for cardiac risk factors, AVC progression was not independently associated with decreasing FMD% or increasing biomarkers [OR FMD% 1.105 (0.835, 1.463), CRP 1.014 (0.849, 1.210), vWF% 1.132 (0.559, 2.292), PAI 1.124 (0.960, 1.316), fibrinogen 0.909 (0.338, 2.443), IL6 1.061 (0.772, 1.459), E-selectin 0.794 (0.426, 1.480) and ICAM-1 0.998 (0.476, 2.092)]. Conclusions: Endothelial dysfunction by FMD% and biomarkers is not significantly associated with the prevalence or progression of aortic valve calcification after adjustment for cardiac risk factors. Highlights: Endothelial dysfunction (ED) is a systemic disorder and a key variable in the pathogenesis of atherosclerosis. We investigated whether MESA participants with ED were more likely to have aortic valve calcification (AVC). ED measured by biomarkers and flow mediated dilationwas not significantly associated with prevalence or progression of AVC.